Caenorhabditis elegans as a Screening Platform for Anti-aging Compounds - Mytilinaiou, Eirini; Kitopoulou, Katerina; Palikaras, Konstantinos (Methods Mol Biol (Clifton, N.J.), 2025)
As global life expectancy continues to rise, the need to understand and mitigate the effects of aging on human physiology has become increasingly important. Aging is characterized by cellular and functional decline, resulting in a higher prevalence of chronic diseases. Model organisms, such as Caenorhabditis elegans, provide valuable insights into the molecular mechanisms underlying aging and serve as platforms for developing potential therapeutic interventions. This chapter highlights the utility of C. elegans in aging research by presenting three straightforward protocols: the lifespan assay, thrashing assay, and lipofuscin accumulation assay. These assays are designed to effectively assess key physiological aspects of organismal health and provide a reliable framework for monitoring the aging process and evaluating anti-aging compounds. Here, we demonstrate the application of these protocols using Urolithin A as an example, underscoring their efficacy in advancing our understanding of aging and contributing to the development of potential interventions.
Keywords: Aging; Anti-aging compounds; Body bending; Caenorhabditis elegans; Lifespan; Lipofuscin; Nematode; Thrashing